2001
DOI: 10.1046/j.1365-294x.2001.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis of genetic variation among and within Alpine marmot populations in the French Alps

Abstract: The genetic structure of the Alpine marmot, Marmota marmota, was studied by an analysis of five polymorphic microsatellite loci. Eight locations were sampled in the French Alps, one from Les Ecrins valley (n = 160), another from La Sassière valley (n = 289) and the six others from the Maurienne valley (n = 139). Information on social group structure was available for both Les Ecrins and La Sassière but not for the other samples. The high levels of genetic diversity observed are at odds with the results obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 57 publications
3
32
1
1
Order By: Relevance
“…Similarly, the four North American species are believed to be evolutionarily equidistant from M. marmota (Kruckenhauser et al 1999;Steppan et al 1999) and so could be expected to have inherited similar variation at the loci developed for M. marmota. We examined all studies in which genetic variation at subsets of the Spermophilus or M. marmota loci was examined in M. olympus, M. caligata, M. flaviventris, and M. marmota; all authors (Goossens et al 1998(Goossens et al , 2001da Silva et al 2003;Floyd 2003;Kruckenhauser and Pinsker 2004;Kyle et al 2004;Cohas et al 2006;Griffin 2007) reported substantially greater diversity in terms of numbers of alleles per polymorphic locus and both observed and expected heterozygosities than we found across the entire population of Vancouver Island marmots. Thus, having eliminated the possibility of ascertainment bias, our results indicate that across its entire range, the gene pool of M. vancouverensis contains only a small fraction of the neutral genetic variation that other Marmota species carry.…”
Section: Genetic Diversity Of Vancouver Island Marmotsmentioning
confidence: 99%
“…Similarly, the four North American species are believed to be evolutionarily equidistant from M. marmota (Kruckenhauser et al 1999;Steppan et al 1999) and so could be expected to have inherited similar variation at the loci developed for M. marmota. We examined all studies in which genetic variation at subsets of the Spermophilus or M. marmota loci was examined in M. olympus, M. caligata, M. flaviventris, and M. marmota; all authors (Goossens et al 1998(Goossens et al , 2001da Silva et al 2003;Floyd 2003;Kruckenhauser and Pinsker 2004;Kyle et al 2004;Cohas et al 2006;Griffin 2007) reported substantially greater diversity in terms of numbers of alleles per polymorphic locus and both observed and expected heterozygosities than we found across the entire population of Vancouver Island marmots. Thus, having eliminated the possibility of ascertainment bias, our results indicate that across its entire range, the gene pool of M. vancouverensis contains only a small fraction of the neutral genetic variation that other Marmota species carry.…”
Section: Genetic Diversity Of Vancouver Island Marmotsmentioning
confidence: 99%
“…This phenomenon has long been recognized and is referred to as inbreeding depression (Darwin 1868;Charlesworth & Charlesworth 1987), and is thought to be one of the primary selective forces opposing the build-up of deleterious recessive mutations (Lynch 1993). Avoidance of inbreeding has probably played a major role in the evolution of dispersal and breeding behaviours (Brooker et al 1990;Clutton-Brock 1989;Dobson et al 1997;Goosens et al 2001;Keane 1990), and has implications for many areas of biology including conservation (O'Brien 1994;Hedrick & Kalinowski 2000) and human health (Bellamy et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most genetic studies within social units report a higher proportion of heterozygotes than expected under random mating [i.e., evidence for heterozygote excess (outbreeding)]. This finding was described, for example, in yellow-bellied and alpine marmots (30,31), white-tailed deers (32), and in black-tailed prairie dogs (33).…”
mentioning
confidence: 99%